As percepções dos empresários do setor de reparação automotiva quanto à aliança estratégica "Rede Bom Serviço" - Couto Neto, Milton Henrique do (2004)
The strategical alliances, that once were more common in big conglomerate, have come to small firms. Nowadays, it’s seen uncountable cases of pharmacies, supermarkets, construction supplies and furniture stores chains. In the state of Espirito Santo, some